Can authentic assessment find its place in seafarer education and training?. Issue 4 (2nd October 2017) - Ghosh, Samrat
ABSTRACT: Evidence from past research suggests that decontextualised traditional assessment methods promoted by the STCW Code'95 are failing to address the development of skills considered essential by seafarer employers and leading to overall student disengagement. Authentic assessments conducted in real-world contexts and requiring an integration of competence will assess a seafarer's competence to perform tasks at workplace standards. However, there is absence of research on authentic assessment in seafarer education and training (SET). The assessment methods adopted by maritime education and training (MET) institutes to assess a seafarer's competence is directed by the requirements of the STCW Code. Hence, this paper analyses assessment methods (training ships, in-service experience, simulator, laboratory equipment, practical tests) other than traditional assessments that are recommended by the STCW Code in its effectiveness to implement authentic assessment for SET. The effectiveness of the methods was not only judged on its ability to recreate real-world scenarios but also on the issues of financial costs, task design, and learning effect. This paper concludes to state that authentic assessment can theoretically find its place in SET if the issues highlighted in this paper are addressed. Future research shall provide empirical evidence towards the impact of authentic assessment on student achievement.